(NoSNOWY CITOLOGII (B:s (Nu^EBNOE POSOBIE (B/s - (NmAKAROW(B, (Np(B.(Nw(B.s ((NmOSKWA (B:s (NsOW(B. (NNAUKA(B,s, 1953)
(NzAKL(B. : (NS(B. 499-503s
(NbIBLIOGR(B. (NW KONCE GL(B.s
Keywords: (NcITOLOGIQ(B. (NkLETO^NAQ TEORIQ STROENIQ VIWYH SU]ESTW(B. (NvIWOE DOKLETO^NOE SU]ESTWOs